Autonomous Upgraded Herbicide Sprayer Using Basic Concepts of Artificial Intelligence - VishnusaiR, T.J.Jeyaprabha(M.E), (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper intends to help farmers fight weeds in a better way. This paper is an initiative to design an autonomousupgradedherbicidesprayertopreventtoxiccontamination on healthy food crops and ensure herbicide free food for consumption. The paper suggests simple ideas to upgrade existing herbicide sprayers after analysing advantages and disadvantages of prevailing spraying methods. The aimed working methodology and proposed features of the autonomous upgraded herbicide sprayer are detailed in this paper. Considering the heavy soil compaction that happens due to excess usage of tractors, the overall weight of the proposed herbicide sprayer aims to be of lesser weight and is inspired by the basic design structureof an all-terrain vehicle (ATV). The ATV is proposed to be an autonomous version using navigation sensors, GPS, machine vision, dead-reckoning sensors, laser-based, inertial sensors,and geomagnetic direction sensors. Features like Climate checking technology is also suggested in the proposed herbicide sprayer. The concept of smart spraying technology is marginally altered and inculcated to the proposed herbicide sprayer. To differentiate between a weed and a healthy crop, a smart weed identifier along with an advanced camera is proposed tobe used. To fix the challenge of herbicide being possibly sprayed on nearby healthy crops, a fast-adaptive herbicide sprayer is being included to the proposedsprayer.